Teacher Communication Practices in Trigonometric Instruction: A Comparative Study Across Experience Levels - Tyas, Dewi Kristika Findia Ning; Purwanto, Purwanto; Qohar, Abd.; Sulandra, I Made (FKIP Universitas Lampung, 2024)
Teacher communication is critical in mathematics learning, influencing students’ understanding, engagement, and academic success. This study explores the communication practices of novice, intermediate, and senior mathematics teachers when teaching trigonometric comparisons in right triangles. Using a qualitative exploratory design, classroom observations and interviews were conducted with three vocational high school teachers in Keerom Regency, Papua Province, Indonesia, focusing on five communication aspects: clarity, assertiveness, responsiveness, relevance, and presentation style manipulation. The findings reveal significant differences among the teacher groups. Novice teachers exhibited excellent communication by integrating prerequisite knowledge, employing visual aids, and connecting lessons to real-world applications. Intermediate teachers demonstrated structured but conventional communication methods, focusing on content delivery with limited interactivity. Senior teachers, while experienced and accurate, relied heavily on traditional lecture-based approaches and displayed limited responsiveness to student needs. This study highlights the strengths of novice teachers’ student-centered strategies, such as group activities and guided discovery, which enhanced student engagement and comprehension. The research underscores the need for professional development programs to promote innovative teaching practices across all experience levels. Future studies should examine how professional growth and contextual factors influence teacher communication, contributing to improved mathematics learning outcomes. Keywords: teacher communication, vocational school, trigonometry, teaching experience. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1854-1869